A Case of Acute Eosinophilic Leukemia with a Novel PHF6 Mutation. (5th July 2021) - Lipof, J. J.; Huselton, E. J.; Zent, C. S.; Evans, A.; Zhang, B.; Rothberg, P. G.; Bennett, J. M.
Abstract : Acute eosinophilic leukemia (AEL) is a rare form of acute myeloid leukemia (AML) that requires prompt exclusion of reactive etiologies of eosinophilia and identification of an underlying acute myeloid neoplasm. Myeloid neoplasms with prominent eosinophilia often have rearrangements in the platelet-derived growth factor receptor α ( PDGFRA ) or β ( PDGFRB) or are associated with core-binding factor AML. In this report, we describe a 35-year-old male presenting with chest discomfort and altered mental status, found to have marked leukocytosis with eosinophilic predominance and an elevated blast count. Bone marrow aspirate and biopsy findings were morphologically consistent with AEL. Fluorescence in situ hybridization (FISH) and standard karyotype analysis did not reveal any abnormalities, and mutation analysis using next generation sequencing (NGS) revealed a pathogenic mutation in PHF 6. Cardiac work-up revealed findings suggestive of eosinophilic myocarditis. High-dose glucocorticoid therapy was initiated followed by standard intensive induction chemotherapy with cytarabine and idarubicin. He experienced a rapid reduction in peripheral blood eosinophil and blast count and was found to be in a complete remission at the time of his postinduction bone marrow examination. He underwent allogeneic stem cell transplantation with a matched sibling donor after consolidative high-dose cytarabine and remains in remission at the time of this report, 6 months following his initial diagnosis. The rarity of this condition has resulted in a paucity of data to guide management. Additional studies are needed to better characterize this entity and inform optimal management strategies to attain a long-term sustained remission in these patients.